CD22 is a potential target of CAR-NK cell therapy for esophageal squamous cell carcinoma - Tingdang Liu; Ximing Dai; Yien Xu; Tian Guan; Liangli Hong; Tahir Zaib; Qi Zhou; Ke Cheng; Xiaoling Zhou; Changchun Ma; Pingnan Sun (Journal of Translational Medicine, 2023)
Abstract Background Chimeric antigen receptor NK (CAR-NK) cell therapy is one of the most promising immunotherapies. Although it has shown a significant therapeutic effect in hematologic malignancies, few successes have been obtained in solid tumors including esophageal squamous cell carcinoma (ESCC). The major reasons are lack of specific cell surface antigens and complex tumor microenvironment. Here we identify CD22, a well-known tumor surface marker in hematologic malignancies, is expressed in ESCC, possibly serving as a potential target of CAR-NK cell therapy. Methods The expression of 13 tumor cell surface antigens used clinically was analyzed in patients from The Cancer Genome Atlas (TCGA) database. Also, mRNA expression were detected in 2 ESCC cell lines and 2 patients samples by qCPR. Then according to Venn diagram, CD22 was selected for further investigation. Following this, the expression of CD22 by immunofluorescence (IF) in ESCC cell lines and by immunohistochemistry (IHC) in 87 cases of human ESCC samples was detected respectively. On the basis of H-score results, the correlation between CD22 expression and clinical parameters was analyzed. As a proof, the efficacy of CD22-targeted CAR-NK cells against ESCC cell lines was performed by a real-time cell analyzer (RTCA) platform. Results KYSE-140 and KYSE-150 cell lines displayed surface expression of CD22. IHC showed an 80.46% (70/87) positive rate in ESCC patient samples. Among these, cell membranous expression of CD22 was observed in 27.59% (24/87) patient samples. Through chi-square test, expression of CD22 in ESCC was associated with lymph node metastasis while it was no related to the depth of tumor invasion and clinical stage. Engineered CD22-targeted CAR-NK cells exhibited inhibitory growth capability against ESCC cell lines (p < 0.0001). Conclusions CD22 is a potential tumor surface antigen capable of being targeted by CAR-NK cells in ESCC. And potential therapeutics for ESCC may be developed based on immune cells expressing anti-CD22 CAR. The study also indicates that CD22 CAR-NK cells could be used in other cancers and more in vivo experiments are needed.